(untitled) (Journal of Pharmaceutical Negative Results, 2022)
COVID-19 respiratory viral disease has changed the entire research communities’ focus towards Diseases, Health Care, Treatment and related resources decision making and services. Fuzzy approach gives simplification and improvement in processing logic and speed applied to Data analytics and testing of algorithm for different business purposes may be future research domain. Significant COVID-19 analytics can help to classify and prioritize the resources the future consequences to take enhanced self-ruled decisions, to recognise and design pattern in data spread to design strategic policies for medical, health care units and stakeholders.